Treatment of giant emphysamous bulla with endobronchial valves in patients with chronic obstructive pulmonary disease: a case series - Tian, Qing; An, Yang; Xiao, Bin-Bin; Chen, Liang-An (Journal of Thoracic Disease; Vol 6, No 12 (December 31, 2014): Journal of Thoracic Disease, 2014)
Background: Giant emphysamtous bulla (GEB) can negatively affect the pulmonary functions of chronic obstructive pulmonary diseases (COPD) patients, including decreased forced expiratory volume in 1 s (FEV1) and increased functional residual capacity (FRC). The aim of this study was to evaluate the efficacy of endobronchial valve (EBV) to treat bullae and to find efficacy predictors of successful treatment. Methods: Five COPD patients with giant bulla were treated using EBVs. Before the EBV deployment, collateral ventilation (CV) between the targeted and adjacent lobes was evaluated with Chartis system. Results: In the two patients with negative CV, the mean value of FEV1 increased from 27.1±11.4% of predicted value before EBV treatment to 32.8±12.0% (P>0.05) at 1 month after EBV treatment, than to 31.7±24.5% (P>0.05) at 6 months after EBV treatment. Only one patient, whose bulla occupied the whole right middle lung, displayed sustained improvement of FEV1 at 6 months after EBV treatment. In the three patients with positive CV, the mean value of FEV1 decreased from 28.8±19.0% of predicted value before EBV treatment to 24.8±12.6% (P>0.05) at 1 month after EBV treatment, than to 22.1±10.8% (P>0.05) at 6 months after EBV treatment. Conclusions: EBV is an effective measure to treat highly selected COPD patients with giant bulla. Although, EBV treatment can achieve transient improvement of lung function at patients with CV negative bulla, long-term benefit was merely observed at the patient with a bulla at right middle lobe (RML).